A review of vitamin D deficiency and vitamin D receptor polymorphisms in endocrine-related disorders - Nur Faten Hafizah Rosli; Noor Shafina Mohd Nor; Rose Adzrianee Adnan; Siti Hamimah Sheikh Abdul Kadir (Clinical and Experimental Pediatrics)
The endocrine system is a complex network of glands that produce and release hormones that regulate various physiological processes. In the past few decades, the human skin has been identified as an important peripheral endocrine organ that is the main site for the synthesis of vitamin D through exposure to sunlight. Mutations in downstream vitamin D-related gene pathways are associated with disease development. The vitamin D receptor (VDR) gene, which regulates the pleiotropic effects of vitamin D, has been extensively studied in adult populations. Several studies have reported the prevalence of vitamin D deficiency in children and adolescents. With changes in socioeconomic status and lifestyle, vitamin D-deficient individuals are prone to developing the disease at a young age. However, geographical and racial differences affect the association between VDR gene polymorphisms and vitamin D endocrine disorders, explaining the nonconsensus effects of polymorphisms and their association with disease development across populations. In this review, we discuss the connection between the vitamin D endocrine system and polymorphisms in the gene encoding VDR in children and adolescents, focusing on its effects on growth, puberty, insulin resistance, and the immune system.